Phenotypic Analysis of a Population of IgA+ Cells in the Follicle-Associated Epithelium of Mouse Peyer's Patches - Hernandez, Maria Olga; Mantis, Nicholas J. (PLOS ONE, 2015)
The follicle-associated epithelium (FAE) selectively transports prions, viruses, pathogenic bacteria, commensal microflora, and even secretory IgA (SIgA)-immune complexes from the intestinal lumen to underlying gut-associated lymphoid tissues like Peyer’s patches. The FAE consists of a single layer of columnar epithelial cells that includes enterocytes and M (microfold) cells, intermingled with dendritic cells (DCs), macrophages, and naïve and memory B and T lymphocytes. In this report we describe a population of IgA+ cells that reside within and immediately below the FAE in mouse Peyer’s patches. Immunofluorescence microscopy analysis indicated that the FAE-associated IgA+ cells were negative for surface antigen markers specific for B cells (B220), T cells (CD3), DCs (CD11c), and plasma cells (CD138). The IgA+ cells were also negative Ki-67 and IRF4, indicating that they are not mature B cells or plasma cells. The IgA+ cells were, however, often found in close proximity to DCs, leading us to speculate that the population of IgA+ cells in the FAE constitutes an atypical subset of B cells involved in mucosal antigen surveillance and/or immune recall.